PEWIRA PEWIRA: PENDAMPINGAN WIRAUSAHA PEMULA MELALUI PELATIHAN DIGITAL MARKETING, BROADCASTING, DAN PUBLIC SPEAKING DI PKBM ANGGREK BULAN BANYUWANGI - Yulianingsih, Wiwin; Nugroho, Rivo; Sulistyowati, Raya; Jalal Rosyanafi, Rofik; Mustakim, Mustakim; Susilo, Heryanto; Akmalia Putri, Fina (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2025)
This community service program discusses the PEWIRA program: Mentoring Beginner Entrepreneurs through Digital Marketing, Broadcasting, and Public Speaking Training at PKBM Anggrek Bulan Banyuwangi. The program's background stems from the needs of learners, start-up entrepreneurs, and women's groups for digital marketing and communication skills to increase business competitiveness in the digitalization era, amidst limited access to technology and low digital literacy in the local community. Community Service uses a qualitative-descriptive approach with the Asset-Based Community Development (ABCD) method, which involves mapping community assets, participatory training, and ongoing mentoring. The implementation results show a significant increase in learners' skills in marketing products digitally, creating audio-visual content, and honing public speaking skills. Active participation of participants is seen in the process of creating business accounts on social media, producing visual-based promotional content, and delivering product presentations confidently. Evaluation shows that the majority of participants experienced competency growth, began adopting technology, and building community-based start-up business networks. The PEWIRA program has proven effective in driving social and economic transformation, while strengthening a culture of collaboration and entrepreneurial independence within the Anggrek Bulan Community Learning Center (PKBM) in Banyuwangi. The program's implications include providing a sustainable and inclusive model for empowering budding entrepreneurs, making a significant contribution to increasing digital capacity and strengthening the role of non-formal education in local economic development.